Protocol for a non-randomised pilot and feasibility study evaluating a multicomponent intervention to simplify medication regimens for people receiving community-based home care services. Issue 7 (19th July 2019) - Sluggett, Janet Kathleen; Page, Amy Theresa; Chen, Esa Y H; Ilomäki, Jenni; Corlis, Megan; Van Emden, Jan; Hogan, Michelle; Caporale, Tessa; Angley, Manya; Hilmer, Sarah N; Ooi, Choon Ean; Bell, J Simon
Abstract : Introduction: Managing medication regimens is one of the most complex and burdensome tasks performed by older people, and can be prone to errors. People living with dementia may require medication administration assistance from formal and informal caregivers. Simplified medication regimens maintain the same therapeutic intent, but have less complex instructions and administration schedules. This protocol paper outlines a study to determine the feasibility of a multicomponent intervention to simplify medication regimens for people receiving community-based home care services. Methods and analysis: This is a non-randomised pilot and feasibility study. Research nurses will recruit 50 people receiving community-based home care services. All participants will receive the intervention from a clinical pharmacist, who will undertake medication reconciliation, assess each participant's capacity to self-manage their medication regimen and apply a structured tool to identify opportunities for medication simplification. The pharmacist will communicate recommendations regarding medication simplification to registered nurses at the community-based home care provider organisation. The primary outcome will be a description of study feasibility (recruitment and retention rates, protocol adherence and stakeholder acceptability). Secondary outcomes include the change in number of medication administration times per day, medication adherence, quality of life, participant satisfaction, medication incidents, falls and healthcare utilisation at 4 months. Ethics and dissemination: Ethical approval was obtained from the Monash University Human Research Ethics Committee and the community-based home care provider organisation's ethical review panel. Research findings will be disseminated to consumers and caregivers, health professionals, researchers and healthcare providers through the National Health and Medical Research Council Cognitive Decline Partnership Centre and through conference presentations, lay summaries and peer-reviewed publications. This study will enable an improved understanding of medication management and administration among people receiving community-based home care services. This study will inform the decision to proceed with a randomised controlled trial to assess the effect of this intervention. Trial registration number: ACTRN12618001130257; Pre-results.